Monetary Analysis, the Equilibrium Method, and Keynes's "General Theory" - Kohn, Meir (Journal of Political Economy, 1986)
Compared with the work of his contemporaries, Keynes's General Theory represented a radical change in theoretical method–from sequence analysis to the method of equilibrium. The nature of this change is discussed, together with its implications for the substance of Keynes's message and for the subsequent development of macroeconomics.